Left Ventricular Function Assessment Using 2 Different Cadmium-Zinc-Telluride Cameras Compared with a γ-Camera with Cardiofocal Collimators: Dynamic Cardiac Phantom Study and Clinical Validation - Bailliez, Alban; Lairez, Olivier; Merlin, Charles; Piriou, Nicolas; Legallois, Damien; Blaire, Tanguy; Agostini, Denis; Valette, Frederic; Manrique, Alain (Journal of Nuclear Medicine, 2016)
This study compared two SPECT cameras with cadmium-zinc-telluride (CZT) detectors to a conventional Anger camera with cardiofocal collimators for the assessment of left ventricular (LV) function in a phantom and patients. A gated dynamic cardiac phantom was used. Eighteen acquisitions were processed on each CZT camera and the conventional camera. The total number of counts within a myocardial volume of interest varied from 0.25 kcts to 1.5 Mcts. Ejection fraction was set to 33%, 45%, or 60%. Volume, LV ejection fraction (LVEF), regional wall thickening, and motion (17-segment model) were assessed. One hundred twenty patients with a low pretest likelihood of coronary artery disease and normal findings on stress perfusion SPECT were retrospectively analyzed to provide the reference limits for end-diastolic volume (EDV), end-systolic volume (ESV), ejection fraction, and regional function for each camera model. In the phantom study, for each ejection fraction value, volume was higher for the CZT cameras than for the conventional camera, resulting in a decreased but more accurate LVEF (all P < 0.001). In clinical data, body-surface-indexed EDV and ESV (mL/m(2)) were higher for one of the CZT cameras (Discovery NM 530c) than for the other (D-SPECT) or the conventional camera (respectively, 40.5 ± 9.2, 37 ± 7.9, and 35.8 ± 6.8 for EDV [P < 0.001] and 12.5 ± 5.3, 9.4 ± 4.2, and 8.3 ± 4.4 for ESV [P < 0.001]), resulting in a significantly decreased LVEF: 70.3% ± 9.1% vs. 75.2% ± 8.1% vs. 77.8% ± 9.3%, respectively (P < 0.001). The new CZT cameras yielded global LV function results different from those yielded by the conventional camera. LV volume was higher for the Discovery NM 530c than for the D-SPECT or the conventional camera, leading to decreased LVEF in healthy subjects. These differences should be considered in clinical practice and warrant the collection of a specific reference database.